The Paradigm of Village Development in South Sulawesi in Utilizing Village Funds in the Agricultural Sector. Issue 1 (November 2021) - Zaman, N; Rukmana, D; Fahmid, I M; Jamil, M H
Abstract: Social, economic and ecological development in rural areas is currently the main concern of the Indonesian Government at the national level. This study aims to determine the extent to which village funds are used by the government and village communities for the development of the agricultural sector and the application of the development paradigm in the agricultural sector. The population in this study were all villages in South Sulawesi that received Village Fund assistance from 2015 to 2019. Sampling was based on village classifications according to the Developing Village Index (IDM). Based on the results of the analysis method, it shows that the Village Fund can only be used to fund two of the four activity sectors that can be financed from the Village Fund in the agricultural sector, namely the development sector and the rural empowerment sector. Public. Whereas the application of the development paradigm in each village is based on the village classification using the Village Fund in the agricultural sector, namely: 1) The village is very backward adopting the Post-Structuralist paradigm. 2) under developed villages adopt the Post-Structuralist paradigm. 3) Building the village by adopting the Liberal paradigm. 4) developed villages adopt a liberal a paradigm. 5) independent villages adopt a liberal paradigm.